Enhanced antitumor efficacy through sustained release of 5-fluorouracil from poly(trimethylene carbonate) membranes - Wang, Zongheng; Hou, Zhipeng; Zhang, Shuguang; Ren, Shuangyi; Yang, Liqun; Zhang, Qianshi (Frontiers in Pharmacology, 2025)
IntroductionCancer remains one of the deadliest diseases worldwide. 5-Fluorouracil (5-FU) is one of the most commonly used chemotherapeutic agents in clinical practice today, but its effectiveness is often hampered by rapid drug metabolism and systemic toxicity. To address these limitations, the development of novel drug delivery systems for sustained drug release is essential to improve therapeutic outcomes.MethodsThis study aimed to develop a poly(trimethylene carbonate) (PTMC) membrane capable of sustained drug release of 5-FU to enhance its antitumor activity. The membranes were prepared using the solvent-casting method, and their comprehensive properties were characterized.Results and DiscussionWe evaluated the in vitro sustained release capability, as well as the biocompatibility and antitumor activity at both cellular and animal levels. The results demonstrated that the 5-FU-loaded PTMC membranes exhibited effective sustained release capabilities, superior biocompatibility, and enhanced antitumor effects compared to the 5-FU injections. These findings suggested that the 5-FU-loaded PTMC membranes hold great potential for application in cancer patients, offering benefits in chemotherapy treatment.